Makna Keharmonisan Moderasi Beragama Dalam Tradisi Perang Obor Di Tegalsambi Jepara - Paulina Nirmayazitha Pusparani; Nerita Setyaningtiyas; Andarweni Astuti; Gregorius Sukur (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research seeks deeper information about religious moderation in terms of acceptance of tradition. The research was conducted using a qualitative approach, and several of these methods were intended to obtain information and a clear picture of the focus of the problem discussing religious moderation within the framework of acceptance of tradition. By conducting field observations, interviews, and inputting literacy sources that are relevant to the research theme, the researcher categorizes the data, presents the data, and concludes the data according to the focus of the problem. This study confirms that, religious moderation must be carried out by every human being, because basically in an order in society the realization of harmony is desired, especially in the realization of religious moderation through the implementation of traditions. In carrying out this tradition, the community wants to create unity, brotherhood and harmony by upholding the value of religious moderation as an effort to accept the tradition. They mingle with everyone because this is a form of love and self-awareness as creatures that are able to be tolerant of inter-religious beliefs, so as to create a balanced life in the aim of religious moderation. In establishing social relations, Christians must also not close themselves off. In line with the teachings in the Church's document, Gaudium Et Spes 24. In the perspective of harmony and spirituality of the people in Tegalsambi Village towards tradition, they are not fanatical and exaggerated in their religious practices. Habits and traditions that are still carried out today are factors that increase harmony, harmony and harmony in society. The community feels free, and is given space to channel inspiration, creation, and aspirations in social life. In Javanese terminology, it is commonly referred to as Manunggaling Kawula Gusti, which means life manifested in harmony without any tension or mental disturbance.